Computational Thinking-Based Calculus E-Module to Improve Students' Mathematical Literacy Skills - Aprianti, Siti Nahriah (CV. Strata Persada Academia, 2024)
This research and development are based on the need for teaching materials that are in accordance with the current situation and conditions in the digital era. The purpose of this research is to Develop Computational Thinking-Based Calculus E-Module to Improve Students' Mathematical Literacy Skills that are valid and practical. This type of research is research and development (R&D) through the Analyze, Design, Develop, Implementation and Evaluation stages or also known as the ADDIE model. The research instruments are in the form of e-module validation questionnaires, lecturer and student response questionnaires and student mathematical literacy skills tests. Data analysis was used to obtain results in improving students' mathematical literacy skills through a gain score test. Based on the results of data analysis, it was obtained that 1) the computational thinking-based calculus 1 e-module was declared valid with a value of 0.72 indicating a high validity category, 2) the results of the lecturer response questionnaire of 84.00% and the student response of 81.06% showed that the computational thinking-based calculus E-module was very practical to be used by students and lecturers, and 3) the computational thinking-based calculus E-module was effective in improving students' mathematical literacy skills by the results of the limited trial and the field trial with an N-gain value of 0.74 in the limited trial and 0.77 in the field trial with the high category. Thus, the computational thinking-based Calculus e-module developed is very practical and effective to be used to improve students' mathematical literacy skills.